Penerapan Metode Clustering Untuk Mengetahui Kepatuhan Wajib Pajak Bumi Dan Bangunan Pada Desa Perkebunan Tanjung Keliling - Ratna Cantika; Achmad Fauzi; Anton Sihombing (Asosiasi Profesi Telekomunikasi Dan Informatika Indonesia, 2024)
Land and Building Tax (PBB) is a type of area regulated by the government in determining the amount of tax for implementation and development as well as increasing the prosperity and well-being of the people. Based on taxpayer compliance data in Tanjung Keliling Plantation, the results of tests carried out using the Clustering algorithm can determine the variables of ownership area, hamlet name and payment level. Clusters 1,2,3 of 600 PBB taxpayer data, namely where cluster 1 has 166 data, can be grouped based on the Ownership Area of